2022
DOI: 10.3390/biology11020187
|View full text |Cite
|
Sign up to set email alerts
|

First Descriptive Analysis of the Faecal Microbiota of Wild and Anthropized Barbary Macaques (Macaca sylvanus) in the Region of Bejaia, Northeast Algeria

Abstract: Previous research has revealed the gut microbiota profile of several primate species, as well as the impact of a variety of anthropogenic factors, such as tourist food supply, on these bacterial communities. However, there is no information on the gut microbiota of the endangered wild Barbary macaque (Macaca sylvanus). The present study is the first to characterize the faecal microbiota of this species, as well as to investigate the impact of tourist food provisioning on it. A total of 12 faecal samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Our study could be better designed if a negative control group was considered, especially to assess the absence of bacterial DNA of the used sampling material, even though it is supposed to be sterile [ 23 , 24 ]. However, several studies have not confirmed the sterility of the used material [ 40 , 56 , 61 , 62 ] without it interfering with the interpretation of their results. Moreover, if several samples had been taken at different sites before the uterus incision [ 22 , 23 , 24 , 25 ], such as the veterinary gloves, skin of cows, muscular wound and foetal fluids, this might have aided to the assessment of the origin of the bacteria found in the surgical site.…”
Section: Discussionmentioning
confidence: 99%
“…Our study could be better designed if a negative control group was considered, especially to assess the absence of bacterial DNA of the used sampling material, even though it is supposed to be sterile [ 23 , 24 ]. However, several studies have not confirmed the sterility of the used material [ 40 , 56 , 61 , 62 ] without it interfering with the interpretation of their results. Moreover, if several samples had been taken at different sites before the uterus incision [ 22 , 23 , 24 , 25 ], such as the veterinary gloves, skin of cows, muscular wound and foetal fluids, this might have aided to the assessment of the origin of the bacteria found in the surgical site.…”
Section: Discussionmentioning
confidence: 99%